Challenges in the management of a patient with Cowden syndrome: case report and literature review - Melbārde-Gorkuša Inga; Irmejs Arvīds; Bērziņa Dace; Štrumfa Ilze; Āboliņš Arnis; Gardovskis Andris; Subatniece Signe; Trofimovičs Genādijs; Gardovskis Jānis; Miklaševičs Edvīns (Hereditary Cancer in Clinical Practice, 2012)
Abstract We would like to present a patient with a classical phenotype of a rare disorder - Cowden syndrome, its diagnostics and management challenges. A breast surgeon has to be aware of this rare condition when treating a patient with breast manifestations of Cowden syndrome and has to refer the patient to a clinical geneticist for further evaluation. Sequencing of the PTEN gene showed the Asp24Gly mutation. According to the latest literature data, the lifetime risk of breast cancer for Cowden syndrome patients is 81% and surgery is a justified option to reduce the risk of breast cancer. Bilateral risk-reducing mastectomy with immediate reconstruction was performed to eliminate further risk of breast cancer. 3 years after the risk-reducing breast surgery the patient is satisfied with the outcome. This is to our best knowledge the first reported Cowden syndrome case with follow-up data after risk-reducing measures have been taken.